Prevalence of overweight and obesity in sedentary children and adolescents with or without intellectual disability in the Democratic Republic of Congo - Teddy Bofosa; Betty Miangindula; Constant Nkiama Ekisawa; Guy Bomoko; Kasiam Iasy (Turkish Journal of Kinesiology, 2019)
Overweight and obesity in children and adolescents with intellectual disabilities is a major public health problem. The objective of this study is to estimate the prevalence of overweight and obesity in sedentary children and adolescents with intellectual disability (ID) in Kinshasa. A total of 440 children were selected for this study including 240 with ID (110 girls and 130 boys) and 200 children without ID (91 girls and 109 boys). The present study took place in five educational institutions including 4 special and one normal. The weight and height of the children were measured to allow us to calculate their body mass index. The logistic regression test was used to identify the determinants of overweight or obesity, and to measure the association strength of each determinant (odds ratio). This study reveals that boys with ID are at risk of developing overweight at age 12-14 (odd ratio = 1.33 [0.87-1.18]), 15-17 years (odd ratio = 2), 52 [1.61-2.55]) whereas in girls this risk begins already at the age of 6-11 (odd ratio = 1.28 [0.88-1.91]). With respect to obesity, we found that children with intellectual disabilities presented the risk of obesity at ages 6-11 (odd ratio = 1.84 [1.04-1.85]), 12 -14 years (odd ratio = 1.41 [1.07-1.48]) and 15-17 years (odd ratio = 1.48 [1.23-1.73]). In addition, this study shows that ID subjects were significantly more obese than those with typical development. The risk of overweight and obesity is present in children and adolescents with intellectual disability. We suggest that a program based on diet and exercise can be introduced in Kinshasa special institutions to minimize the risk of overweight and obesity.